Green credit policy and residents’ health: quasi-natural experimental evidence from China - Wang, Mengyu; Wang, Yichun; Guo, Bingnan (Frontiers in Public Health, 2024)
Residents' health plays an important role in economic prosperity and national development. The paper takes the implementation of green credit policy in China as a quasi-natural experiment, and employs the time-varying DID model to evaluate the influence of green credit policy on residents' health. The paper results show that: (1)The green credit policy significantly improves residents' health, and this conclusion still holds after a series of robustness tests. (2) Mechanism analysis reveals that the green credit policy affects residents' health through the improvements of the environment and the elevation of public services standards in demonstration cities. (3) Heterogeneity analysis shows that the impact of green credit policy on residents' health is more significant in the western cities and resource-based cities than in the centraleastern cities and non-resource-based cities. This paper explains the specific path and realization of green credit policy to enhance residents' health, which provides a reference for further designing and improving effective green credit policy.